Morphology and identification of fly eggs: Application in forensic entomology - S. Sanit (2018)
Fly eggs found in corpses can be used as entomological evidence in forensic investigation. This study aims to investigate the morphology of forensically important fly eggs. Eggs of Chrysomya rufifacies, Chrysomya megacephala, Chrysomya pinguis, Chrysomya nigripes, Hypopygiopsis tumrasvini, Lucilia cuprina, Lucilia porphyrina and Musca domestica were examined using 1% potassium permanganate solution for 1 min. Morphometric analysis revealed that the mean length of Hy. tumrasvini (1.63 mm) and C. pinguis (1.65 mm) eggs was the longest, followed by that of L. porphyrina (1.45 mm), C. rufifacies (1.34 mm). The egg length, width of median area and darkness staining of hatching pleats were distinctive features. Four categories of median area were proposed, based on width; (1) distinctly wide (Megaselia scalaris, Synthesiomyia nudiseta); (2) wide (C. nigripes, M. domestica); (3) slightly widening (Hy. tumrasvini, L. cuprina, L. porphyrina); and (4) narrow (C. rufifacies, C. albiceps, C. megacephala, C. pinguis). Four species were examined using SEM, i.e., C. megacephala, C. pinguis, Hy. tumrasvini and L. porphyrina. The eggs of C. megacephala demonstrated swollen hatching pleats. Inside, the hexagon of the chorion appeared as a sponging bumpy feature. The egg of C. pinguis was similar to C. megacephala, except for the sponging bumpy feature on the outer surface of the hatching pleats. Regarding Hy. tumrasvini and L. porphyrina, their island structure was apparent at the inner surface of the upright hatching pleats. The key for identifying these eggs together with other reported species in Thailand has been updated.